The life cycle of Opecoeloides columbellae (Pagenstecher, 1863) n. comb. (Digenea, Opecoelidae): evidence from molecules and morphology - Jousson, O.; Bartoli, P. (International Journal for Parasitology, 2000)
The cosmopolitan digenean family Opecoelidae comprises several hundred species, whose adults live in the digestive tract of marine and freshwater fishes. The genus Opecoeloides Odhner, 1928 is represented in the Mediterranean by a single species, Opecoeloides furcatus (Bremser in Rudolphi, 1819), that has been recorded from six definitive hosts species. To see if this broad host range could be the result of an underestimation of species diversity, we obtained ITS1 ribosomal DNA sequences as well as morphological data from adult specimens of O. furcatus isolated from two definitive hosts species: Mullus surmuletus and Gaidropsarus mediterraneus. Sequence and morphological data were also obtained from several opecoelid cercariae and metacercariae occurring in different invertebrate hosts. The data presented here provide striking evidence that O. furcatus specimens isolated from the two host fishes represent distinct species. This argument is reinforced by the fact that cercariae corresponding to each of these adult species were found in two molluscan host-species, Columbella rustica and Mitrella scripta. These parasite species differ by several nucleotide substitutions and a 60 bp-long insertion in the ITS1. They also show clear morphological differences in testis and ovary shape, as well as in their mean dimensions. Here, we attribute the adult specimens found in G. mediterraneus to Opecoeloides columbellae (Pagenstecher, 1863) n. comb. This species was described and compared with O. furcatus from M. surmuletus. ITS1 sequence comparison allowed identification of the cercaria (occurring in C. rustica) and metacercaria (occurring in Hippolyte inermis) of O. columbellae n. comb.